Hedonic and eudaimonic well-being: the role of resilience beyond fluid intelligence and personality traits - Di Fabio, Annamaria; Palazzeschi, Letizia (Frontiers in Psychology, 2015)
Resilience is a key factor in the well-being of individuals. The present study set out to analyze the role of fluid intelligence, personality traits, and resilience in hedonic and eudaimonic well-being in order to determine the incremental validity of resilience with respect to fluid intelligence and personality traits in 168 Italian high school students. The Advanced Progressive Matrices (APM), the Big Five Questionnaire (BFQ), the Connor-Davidson Resilience Scale (CD-RISC), the Satisfaction With Life Scale (SWLS), the Positive and Negative Affect Schedule (PANAS), the Meaningful Life Measure (MLM), the Authenticity Scale (AS) were administered to the participants in the study. The results showed that resilience added a significant percentage of incremental variance with respect to fluid intelligence and personality traits in relation to life satisfaction, positive affect, life meaning, and authenticity. These results underline the value of resilience in both hedonic and eudaimonic well-being, thus offering new perspectives for research and intervention.